Tolerance and autoimmunity in TCR transgenic mice specific for myelin basic protein - Goverman, Joan (Immunol Rev, 2006)
Summary: T‐cell receptor (TCR) transgenic mice provide the ability to follow the maturation and fate of T cells specific for self‐antigens in vivo. This technology represents a major breakthrough in the study of autoimmune diseases in which specific antigens have been implicated. Proteins expressed within the central nervous system are believed to be important autoantigens in multiple sclerosis, TCR transgenic models specific for myelin basic protein (MBP) allowed us to assess the role of tolerance in providing protection from T cells with this specificity Our studies demonstrate that T cells specific for the immunodominant epitope of MBP do not undergo tolerance in vivo and that TCR transgenic mice are susceptible to spontaneous autoimmune disease. The susceptibility to spontaneous disease is dependent on exposure to microbial antigens, MBP TCR transgenic models expressing TCRs specific for the same epitope of MBP but utilizing different V(α) genes exhibit differing susceptibilities to, spontaneous disease. These data support the idea that genetic and environmental differences play a role in susceptibility to autoimmunity MBP TCR transgenic models are playing an important role in defining mechanisms by which infectious agents trigger autoimmune disease as well as defining mechanisms by which tolerance is induced to distinct epitopes within self‐antigens.